Effect of Sodium Bicarbonate Solution Mouth Rinse on Salivary Immunoglobulin A (IgA) Levels - Erma Mahmiyah; Jojok Heru Susatyo; Neny Setiawaty Ningsih; M. Ibraar Ayatullah; Amani A Barka (Public Health of Indonesia, 2026)
Background: Gargling with baking soda stimulates parasympathetic nerves in the brainstem's salivatory nuclei, enhancing saliva flow through taste and tactile stimulation. Objective: This study aims to analyzes the effects of sodium bicarbonate mouth rinses on salivary immunoglobulin A (IgA) levels, flow rate, volume, pH, and viscosity. Methods: A Pre and Post-Control Group Design was employed, involving 42 respondents divided into three groups: a control group using 0.1% povidone iodine, a first treatment group using 1% baking soda, and a second treatment group using 2% baking soda. Participants gargled twice daily for 14 days. Results: Results show that a 1% sodium bicarbonate solution significantly reduced salivary IgA levels, flow rate, and volume while increasing pH and viscosity, suggesting a decrease in immune response and potential anti-inflammatory effects. The 2% sodium bicarbonate solution significantly affected flow rate and volume, whereas the 0.1% povidone iodine solution influenced pH and volume. These findings highlight the effectiveness of sodium bicarbonate as an oral rinse for modulating salivary composition and immune activity. Conclusion: In conclusion, a 1% sodium bicarbonate solution demonstrated the most comprehensive effects, reducing IgA levels and altering saliva properties in ways that may benefit oral health by mitigating inflammation. The 2% solution primarily affected saliva production, while povidone iodine impacted pH and volume. This study suggests that sodium bicarbonate mouth rinses, particularly at 1%, could serve as an effective strategy for regulating oral immune responses and maintaining oral health. Keywords: Sodium Bicarbonate;  Immunoglobulin A;  pH; Salivary; Viscosity